URGENSI KESADARAN HUKUM DALAM PERLINDUNGAN MEREK DAGANG UMKM DI INDONESIA - MB, Sandy Alun Samudra; Supian, Ujang; Ramadhan, Taufik Ismail; Hilmawan, Ahmad Roja; Yusup, Candra Maulana Mochamad (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Trademark protection is a crucial aspect in ensuring the sustainability and competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. However, the legal awareness of MSME actors regarding the importance of trademark registration and protection is still relatively low, thus creating potential disputes and business losses. This study aims to explain the legal aspects that regulate trademarks in Indonesia, analyze the gap in legal awareness among MSME actors, and evaluate government efforts in encouraging trademark registration. The methodology used is a normative legal approach with a literature study approach. The results of the study indicate that the low level of legal understanding, registration fees that are considered expensive, and minimal socialization are the main obstacles in protecting MSME brands. The government has taken a number of steps such as simplifying procedures and subsidizing registration fees, but their implementation has not been evenly distributed. This study recommends increasing legal education on an ongoing basis, integrating trademark protection into MSME empowerment programs, and active collaboration between the government, academics, and MSME associations as practical and strategic solutions in strengthening legal awareness in this sector.